World Bank Research Digest, Vol. 10(1) - World Bank (Washington, DC, 2015)
This issue includes the following headings: Climate Change and Rural Livelihoods in Bangladesh; Natural Disasters and Household Well-Being; Road Improvement and Deforestation, Pathways toward Zero-Carbon Electricity; The Need for Broader Information in Climate Change Assessment; Effectiveness of Protected Areas; and Vulnerability to Malnutrition in the West African Sahel